ISLAMIC FINANCIAL INCLUSION ACCELERATION THROUGH PEER-TO-PEER FINANCING FINTECH - Prameswara Samofa Nadya; Alindha Farezha Nasution; Muhammad Iqbal (Proceeding International Seminar of Islamic Studies, 2023)
This research aimed to examine how far peer-to-peer financing fintech pushes the inclusion of Islamic finance in Indonesia, analyzed by literature review with secondary data from articles, news, and others. The result shows that Islamic fintech problems can be divided into four groups, specifically: regulation, infrastructure, literacy, and management. The solutions are: giving special attention to fintech regulations, especially Islamic fintech, increasing infrastructure quality such as internet network and data security, synergizing between regulators and practitioners of Islamic fintech to organize the literacy program, also focusing on human capital development in supporting Islamic fintech sustainability.